2020
DOI: 10.3389/fphar.2020.00173
|View full text |Cite
|
Sign up to set email alerts
|

Jiang Tang Xiao Ke Granule Protects Hepatic Tissue of Diabetic Mice Through Modulation of Insulin and Ras Signaling – A Bioinformatics Analysis of MicroRNAs and mRNAs Network

Abstract: Objective: To investigate the impact of JTXK granule on the miRNA expression profiles in hepatic tissue of diabetic mice, and to explore the molecular targets and associated signaling pathways of JTXK granule in its anti-diabetic effect.Methods: Eight mice were randomly selected as normal group fed with chow diet. Then high fat diet was used to induce diabetic model, and the mice were subsequently divided into JTXK-treated group (J group, n = 6) and model group (M group, n = 6). After 8 weeks' intervention we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…The first part focuses on determining whether MPM can effectively identify the morphological differences between normal, fibrosis and cancer tissues. As shown in the first row of Figure 2, the hepatocytes in normal tissues arrange radially around the central vein, and the cords of hepatocytes keep regular arrangement as previously reported [20]. Hepatocytes are normal in shape with nuclei located in the center (yellow arrow in Figure 2A2).…”
Section: Resultssupporting
confidence: 75%
“…The first part focuses on determining whether MPM can effectively identify the morphological differences between normal, fibrosis and cancer tissues. As shown in the first row of Figure 2, the hepatocytes in normal tissues arrange radially around the central vein, and the cords of hepatocytes keep regular arrangement as previously reported [20]. Hepatocytes are normal in shape with nuclei located in the center (yellow arrow in Figure 2A2).…”
Section: Resultssupporting
confidence: 75%
“…Lin et al demonstrated that miR-199a-5p is upregulated in pancreatic β cells in response to high glucose and promotes apoptosis and ROS generation in type 2 diabetes ( 38 ). In addition, a bioinformatics analysis showed that mmu-miR-199a-5p is closely related to inflammatory response, and insulin signal pathway in the liver of diabetic mice ( 39 ). SHP2 is a widely expressed SH2 domain-containing protein tyrosine phosphatase ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…(Huanglian), Salvia miltiorrhiza Bunge (Danshen), and so on, is a classic formula from traditional Chinese medicine. Our previous studies have shown that JTXK granules exhibited an overt therapeutic effect in the management of diabetes through the improvement of glucolipid metabolism, protection of islet ßeta-cells, and inhibition of oxidative stress and inflammatory reactions in various organs and tissues [ 15 18 ]. There are studies supporting that the main active ingredients from this herbal formula, for example, berberine and ginsenoside Rb1, are capable of activating AMPK signaling [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%